TikTok as Microlearning: Unveiling Vocational Students’ Experiences in Learning Computer Systems - Sukma Larasati; Aris Budianto; Febri Liantoni; Saida Ulfa (Yayasan Keluarga Guru Mandiri, 2026)
This study aims to explore the learning experiences of vocational high school students in using TikTok as a microlearning medium for computer systems. The study aims to identify the factors that support or inhibit this process. The study used a qualitative descriptive approach. Data were collected through questionnaires and in-depth interviews with 10th-grade students at a vocational high school in Surakarta. Data analysis was conducted thematically based on three aspects: Cognitive Strategies, Efforts, and Metacognitive Strategies. The results indicate that using TikTok in learning provides a positive learning experience. This positive outcome is due to TikTok's concise, visual, and easily accessible content. Students can learn independently through short videos, create summaries, engage in peer discussions, and manage their study time. Inhibiting factors also include distractions from non-educational content and the videos' limited depth of information. In conclusion, TikTok has the potential to be an effective microlearning platform for vocational high school students, particularly for learning computer systems. The implications of this study's findings fill a gap in the literature, particularly regarding TikTok-based microlearning for productive subjects in vocational education.